The early moments of Social Help and its buildings for childhood. The press as a means of propaganda - Cristina González Maza (El Futuro del Pasado, 2010)
The aim of this work is the study of Social Help, one of the most important aid organizations and greater activity in the recent past in Spain.Emerged to meet the needs of a population without means for the devastating effects of war. Of all the buildings for the poor, large numbers were intended for children's world.To better understand the operation of this organization, besides the consultation of somemonographs, managing the local press has been a great help, since it is a reflection of the society in wich it arises.